Microstructural fracture mechanics: Stored energy density at fatigue cracks. (January 2021) - Xu, Yilun; Wan, Weifeng; Dunne, Fionn P.E.
Abstract: This paper addresses the mechanistic drivers of short fatigue crack growth using theory, computational crystal plasticity and experimental test and characterisation. The asymptotic theory shows that the crack tip stored energy density is non-singular and finite and can be related to stress intensity, but unlike the latter, it depends on the crystal Burgers vector and intrinsic slip strength. The computational methods allow the stored energy to be calculated accurately at crack tips and show that good agreement is obtained for static cracks with the theory. The experiments allow the crack tip stored energy to be measured, demonstrating intimate microstructural sensitivity, direct correlation with experimental crack growth variations and good quantitative agreement with both asymptotic theory and computational modelling. Hence a new microstructurally-sensitive fracture mechanics has been presented in the context of short cracks within crystalline materials.